If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 800X + -5E + -15 Reorder the terms: 14 = -15 + -5E + 800X Solving 14 = -15 + -5E + 800X Solving for variable 'E'. Move all terms containing E to the left, all other terms to the right. Add '5E' to each side of the equation. 14 + 5E = -15 + -5E + 5E + 800X Combine like terms: -5E + 5E = 0 14 + 5E = -15 + 0 + 800X 14 + 5E = -15 + 800X Add '-14' to each side of the equation. 14 + -14 + 5E = -15 + -14 + 800X Combine like terms: 14 + -14 = 0 0 + 5E = -15 + -14 + 800X 5E = -15 + -14 + 800X Combine like terms: -15 + -14 = -29 5E = -29 + 800X Divide each side by '5'. E = -5.8 + 160X Simplifying E = -5.8 + 160X
| (x+2)*x+3=24 | | 1/3-1/9x=-5/3 | | 2/11y+1/4=1/11y+8/5 | | 2ac-3bc-6bd+4ad=0 | | ac-3bc-6bd+4ad=0 | | (6x+8)(5x^2+9x+2)= | | x*x+7x+5=0 | | 5x^2+51x-360=0 | | -9p-7=10p | | x^4+2x^3=21-14x-4x^2 | | 9xy^4-xz^2=0 | | 2y^4=11y^2-12 | | f(5)=7(5)-22/4 | | Tan3.14/12 | | X+58=120 | | X-25=80 | | 9y-38=-8(y-8) | | (9x^2-5x-42)+(4x^2+7x)= | | -3x+5=-6x+14 | | (-3)+x=10 | | (2x+5)(6-3x)=0 | | 7x+4y+2z=1650 | | 6(x-2)=35 | | x^5-3*x^3=0 | | x^2+y^2+10x-14y+6=0 | | x*y=351 | | 6x+4y+3z=63 | | 3x+62=9x-10 | | px-qx=n | | Sec(x-pi/4) | | 0=-240 | | -4(2y+3)=-18 |